(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Distribution and ecology of two new for Ukraine lichen species (Toninia physaroides(Opis) Zahlbr.and Caloplacamuscorum(A.Massal.) M.Choisy& Werner) and 14 rare speciesfrom nature reserve“Yelanetsky Step” are elucidated in the article.